1. TITI SURIANI: Implementasi Aplikasi Ruang Guru Di Sma Islam Al-Falah Kota Jambi Tahun Ajaran 2023-2024 - Suriani, Titi; Purnomo, Budi; Siregar, Isrina (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
ABSTRACT The purpose of this research is to find out that there are several problems with the use of the Ruang Guru application by the students who use it, their lack of understanding of the purpose and objectives of the application and their learning achievement is not yet optimal, so they decide to join the tutoring of the Ruang Guru application. . This research method uses qualitative research with descriptive research type. The data collection techniques in this research are observation, interviews and documentation. By using research indicators about what applications are available in the teacher's room which are adapted to history learning material. The results of the research show that the use of the teacher's room application has a positive impact on students' interest in learning and researchers know what the deficiencies in the teacher's room application are so that they can hinder the student's learning process. With the applications and features in the teacher's room, it is hoped that students will be able to learn independently and practice good questions to improve their learning achievement, but the problem that the researchers found was that the discussion room feature was not implemented quickly enough so that when students were working on assignments it took some time. to get answers. This research can be concluded that the use of the teacher's room application is very effective for students' independent learning at home, because it does not require additional costs for transportation outside the house, and is time efficient because students can study independently at home with their respective smartphones. Apart from that, the problem is that there are several features that are not fast enough to respond or respond, such as the discussion room feature.